Increased serum concentrations of advanced glycation end products: a marker of coronary artery disease activity in type 2 diabetic patients. Issue 1 (1st January 2001) - Kiuchi, K; Nejima, J; Takano, T; Ohta, M; Hashimoto, H
Abstract : OBJECTIVE: To assess whether the concentrations of serum advanced glycation end products (AGE) in diabetic patients with obstructive coronary artery disease differ from those in type 2 diabetic patients without obstructive coronary artery disease. DESIGN: Serum AGE concentrations were measured in type 2 diabetic patients and in non-diabetic patients, both with and without obstructive coronary artery disease, and the relation between these values and coronary disease severity was evaluated. RESULTS: Mean (SD) serum AGE concentrations were higher (p < 0.0125) in type 2 diabetic patients with obstructive coronary artery disease (5.5 (2.5) mU/ml, n = 30) than in patients without obstructive coronary artery disease (2.8 (0.5) mU/ml, n = 12), and higher than in non-diabetic patients with (3.4 (1.0) mU/ml, n = 28) and without (3.2 (0.4) mU/ml, n = 13) obstructive coronary artery disease. Serum AGE was associated with the degree of coronary arteriosclerosis in type 2 diabetic patients with obstructive coronary artery disease (single vessel: n = 13, 3.4 (0.9) mU/m; two vessel: n = 6, 5.7 (1.6) mU/m; three vessel: n = 11, 7.2 (2.5) mU/ml). Serum AGE was positively correlated with serum mean four year HbA1C ( r  = 0.46, p < 0.01), but not with recent serum HbA1C ( r  = 0.24). The four groups did not differ in the other coronary risk factors. CONCLUSIONS: Serum AGE concentrations may be associated with long term poor glycaemic control and reflect the severity of coronary arteriosclerosis in type 2 diabetic patients.